The Effective Management of Fever in Pediatrics and Insights on Remote Management: Experts' Consensus Using a Delphi Approach - Chiappini, Elena; Vitale, Antonio; Badolato, Raffaele; Becherucci, Paolo; Careddu, Domenico; Di Mauro, Antonio; Doria, Mattia; Staiano, Annamaria (Frontiers in Pediatrics, 2022)
Background: Even after the publication of the 2017 update of Italian guidelines on treatment of fever in pediatrics, some fundamental questions are still open and new ones emerged during the COVID-19 pandemics. Objective: To assess the level of consensus among Italian pediatricians on different topics related to treatment of fever in children by using the Delphi technique. Methods: A Delphi study was undertaken between June and September 2021, when two questionnaires were consecutively sent to a panel of experts to be answered anonymously. Results: A first-round questionnaire was sent to 80 pediatricians selected from different Italian regions. Of the 75 respondents (23% working in hospital and 72% outside), 24% were from northwestern, 9% northeastern, 12% central, and 55% southern Italy or islands. A second-round questionnaire was sent to all the first-round respondents, and a response was received from 69 of them. All the statements that reached the pre-defined cut off for consensus (75% or more) concerned the topics of therapeutic appropriateness and management of the febrile child and future prospects in remote management. Only one statement concerning management of the febrile child in the presence of other diseases did not achieve the consensus even after the second round. Conclusions: Italian pediatricians agree on several aspects of treatment of febrile children and their expert opinions could support everyday decision process complementary to recommendations by regulatory agencies and guidelines.